Construction Of Mathematics Materials Through Lesson Study Supported By ICT-Based Learning Media In MGMP Mathematics of SMP Negeri District X Koto Solok District - Dina Agustina (Pelita Eksakta, 2023)
Based on observations and discussions with several mathematics teachers at Singkarak State Middle School, X Koto Singkarak District, Solok Regency, problems were found in learning mathematics, namely students still had difficulty understanding mathematical concepts and students were less active in the learning process. An indication of this is the low student learning outcomes. Teachers still do not utilize learning models and media that can attract students' interest in learning. Conducted training on strengthening mathematics material through ICT-based lesson study. The results showed that there was an increase in the teacher's understanding of the material, the teacher's skills in making learning media and the teacher's proficiency in using IT-based learning media.